Pendampingan Literasi Membaca untuk Meningkatkan Motivasi Siswa Kelas Rendah di MIS Darul Ulum Palangkaraya - Fitriyanti Fitriyanti; Istiyati Mahmudah; Nur Laila Agustina (Jurnal Informasi Pengabdian Masyarakat, 2024)
Education is an effort to create an atmosphere in learning and the learning process so that students can develop their potential to have abilities, literacy is the language skills possessed by a person to communicate, whether in terms of reading, speaking, listening and writing, in different ways according to the goal. Language skills are an ability that a person has in using language, language skills include listening skills, speaking skills, reading skills and writing skills. Reading is one of the skills learned at school age. Reading is one of four language skills, reading is an activity carried out to obtain information contained in reading material